2020
DOI: 10.1186/s12879-020-05543-0
|View full text |Cite
|
Sign up to set email alerts
|

Is the superbug fungus really so scary? A systematic review and meta-analysis of global epidemiology and mortality of Candida auris

Abstract: Background Candida auris is a new pathogen called “superbug fungus” which caused panic worldwide. There are no large-scale epidemiology studies by now, therefore a systematic review and meta-analysis was undertaken to determine the epidemic situation, drug resistance patterns and mortality of C. auris. Methods We systematically searched studies on the clinical report of Candida auris in Pubmed, Embase and Cochrane databases until Oct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
87
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(101 citation statements)
references
References 77 publications
11
87
1
2
Order By: Relevance
“…While the majority of identified C. auris isolates display intrinsic resistance to azoles such as fluconazole, susceptibilities to other antifungals strongly vary among clades. Recent studies demonstrated that clade II isolates (East Asian clade) show the highest degree of antifungal susceptibilities, while clade I strains (South Asian clade) show the lowest susceptibility (Arendrup et al, 2017;Szekely et al, 2019;Chen et al, 2020;Chow et al, 2020). In line with this, resistance to the polyene amphotericin B (AmB) was mainly detected in clade I and clade IV (South America clade) isolates (Chow et al, 2020).…”
Section: Introductionmentioning
confidence: 83%
“…While the majority of identified C. auris isolates display intrinsic resistance to azoles such as fluconazole, susceptibilities to other antifungals strongly vary among clades. Recent studies demonstrated that clade II isolates (East Asian clade) show the highest degree of antifungal susceptibilities, while clade I strains (South Asian clade) show the lowest susceptibility (Arendrup et al, 2017;Szekely et al, 2019;Chen et al, 2020;Chow et al, 2020). In line with this, resistance to the polyene amphotericin B (AmB) was mainly detected in clade I and clade IV (South America clade) isolates (Chow et al, 2020).…”
Section: Introductionmentioning
confidence: 83%
“…As of 15 February 2021, 47 countries have reported a single case or cluster of cases or outbreaks of C. auris infections, according to the Center for Disease Control and Prevention (CDC) of the United States of America ( accessed on 31 March 2021). The epidemiology of invasive C. auris infections has seen dramatic changes, as the sporadic invasive infections from the early years have now been replaced by nosocomial outbreaks that are being reported more frequently and appear to involve an increasing number of patients [ 29 , 30 , 31 , 32 , 37 , 38 , 39 ]. Studies have shown that once C. auris is introduced into a healthcare facility, it spreads rapidly among susceptible patients [ 40 , 41 ].…”
Section: Epidemiology Of C Auris Infectionsmentioning
confidence: 99%
“…C. auris has several unique characteristics, which include its ability to persist, despite the use of common disinfectants, and remain viable for several months, likely due to biofilm formation on plastic surfaces, the hospital environment, and medical devices [ 68 , 69 , 70 ]. Furthermore, very high rates of resistance to fluconazole and variable susceptibility to other azoles, amphotericin B, and echinocandins make the management of C. auris infections extremely difficult [ 37 , 56 , 57 , 58 , 71 , 72 , 73 ]. Crude mortality rates varying from 0 to 72% have been reported among C. auris -infected patients in different studies [ 29 , 30 , 31 , 32 , 37 , 48 , 52 , 56 , 57 , 58 , 74 ].…”
Section: Epidemiology Of C Auris Infectionsmentioning
confidence: 99%
See 2 more Smart Citations